Frecuency of mental disorders and their sociodemographic characteristics in patients with COVID-19 hospitalized in a psychiatric hospital in Lima - Villanueva, Daphne (2023)
Introduction. The description of the characteristics and diagnoses of psychiatric patients with COVID-19 during the pandemic has been poorly described in Peru. Objective. To describe the frequency of mental disorders and the associated sociodemographic characteristics of patients with a positive antigen test for COVID-19 in a peruvian psychiatric hospital from July 2020 to July 2021. Methods. For this descriptive study we analyzed 100 medical records of patients between 18 and 70 years old. The variables studied were the diagnosis according to ICD-10 and sociodemographic features such as age, gender, educational status, employment, days of admission. Results. The most common diagnoses were “Schizophrenia, schizotypal disorders and delusional disorders” (49%) and “mood disorders” (37%), 66% belonged to the lowest socioeconomic levels and 60% were recurrent patients. The month of April 2021 presented the highest number of admissions (n=15). Conclusion. In a year of observation during the COVID-19 outbreak, 100 patients with psychiatric diagnosis who also had SARS-CoV-2 infection were admitted to a reference psychiatric hospital, most of these patients had psychotic disorders.